Soymilk Formula Increases Estrogen and Reduces Testosterone Level in Male Infant White Wistar Rats - Eveline Margo; Wimpie Pangkahila; I Gusti Made Aman (Cell and BioPharmaceutical Institute, 2019)
Background: Children’s immunity system is relatively lower on first year of life, causing atopic babies, leading to allergy. Ideally, newborn babies are given breast milk as main food source on the first 6 months, but often being replaced with cow milk which can induce Cow’s Milk Protein Allergy. For the alternative can replace it with soymilk formula which contains phytoestrogen from isoflavon, which works just like estrogen. The aim of this study to determine whether administration of soymilk formula is capable on increasing estrogen level and reducing testosterone level on male infant white Wistar rats (Rattus norvegicus).Materials and Methods: This research used post test only control group design. Samples were consisted of 36 infant male white Wistar rats aged 7 days, weighing from 10-15 grams, divided into 2 groups, control group which was given cow’s milk and intervention group which was given soymilk. Each group were given intervention with the dose 5% of BW (grams), given twice-a-day orally for 21 days, and subsequently in the morning their blood samples were taken to examine the level of estrogen and testosterone hormone.Results: The study showed that the level of estrogen on intervention group was significantly higher than the control group with mean estrogen level of 0.55±0.03 pg/mL in the control group and 0.82±0.01 pg/mL in the intervention group, while the mean testosterone level was significantly lower on intervention group compared with control group (p<0.05) with 3.25±0.15 ng/mL on control group and 2.36±0.22 ng/mL on intervention group.Conclusion: Soymilk was able to increase estrogen level and reduce testosterone level on male infant white Wistar rats (Rattus norvegicus).Keywords: soymilk formula, estrogen, testosterone, male infant rats